Conversion of Organic Matter in Coal by Photocatalytic Oxidation with H2O2 over SFC/TiO2 in Isolated Oxygen System. (24th October 2019) - Xie, Heng-Shen; Zong, Zhi-Min; Wang, Yu-Gao; Zhao, Pei-Zhi; Zhang, Shi-Hua; Wang, Jun-Qiang; Fu, Hong; Liang, Shuang-Hua; Su, Ling; Wei, Xian-Yong
Abstract : Shenfu bituminous coal (SFBC), Geting coal (GTC), Shengli lignite (SLL), and Holingola coal (HLGLC) were oxidized by UV light radiation with aqueous H2 O2 over SFC/TiO2 in a closed suspension system (CSS) to understand structural characteristics of 4 typical Chinese coals. Raw and oxidized coals were dried and extracted with acetone thoroughly to ensure residue extraction. Meanwhile, the extracts were analyzed using a gas chromatograph/mass spectrometer. The results show that organic matters (OMs) in coals can be converted into a large number of oxygen-containing organic compounds (OCOCs), mainly containing ketones, esters, alcohols, etc. Oxidizing species such as hydroxyls, hydroperoxyl, and alkyl radicals are excited by light irradiation and substitute for hydrogen atoms of methyls and methylenes of acenes or branched-chain alkanes in coals. Acetic acid and acetaldehyde can be formed and dissolved in aqueous solution in the oxidation reaction. The yields can be improved with the enhancement of the oxidation effect.